Domestic Tourist Travel Patterns in Greater Bandung Area: A Geography and Human Mobility-Based Analysis - Bintari Pangesti Putri; Eko Susanto (Journal of Event, Travel and Tour Management, 2026)
This study examines the demographic, behavioral, and spatial dimensions of domestic tourist mobility in the Greater Bandung Area, Indonesia. Using a mixed-methods design, data were collected through field-based surveys, direct observation, and participatory group research conducted at multiple tourism destinations, including Farmhouse Lembang, Kawah Putih, Gedung Sate, and Grey Art Gallery. A total of 180 respondents participated in the study. Analytical interpretation combines Leiper's Tourism System framework with concepts from human geography, particularly spatial interaction and the production of tourism space. Findings reveal that domestic tourists are predominantly young (18–25 years), female, unmarried, and either students or early-career workers with limited travel budgets. Their trips are typically short, spontaneous, and driven by recreational, culinary, and aesthetic experiences shaped by social media. Spatial analysis identifies a radial mobility pattern, with Bandung City functioning as both a tourism hub and a transit node connecting peripheral destinations such as Lembang and Ciwidey. The study also highlights the digitally mediated construction of tourism space, where online representations and social interactions create hybrid zones that merge everyday life with tourist consumption. This research contributes to the understanding of urban–regional tourism systems in emerging economies by integrating behavioral insights with spatial analysis. It underscores the need for sustainable transport planning, digital engagement strategies, and equitable development across underutilized peri-urban destinations.